Prevalence of 16S rRNA Methylation Enzyme Gene armA in Salmonella From Outpatients and Food - Lu, Xin; Zeng, Mei; Zhang, Ning; Wang, Mengyu; Gu, Baoke; Li, Jiaqi; Jin, Huiming; Xiao, Wenjia; Li, Zhe; Zhao, Hongqun; Zhou, Haijian; Li, Zhenpeng; et al. (Frontiers in Microbiology, 2021)
Salmonella is the primary cause of community-acquired foodborne infections, so its resistance to antimicrobials, such as aminoglycosides, is a public health issue. Of concern, aminoglycoside resistance in Salmonella is increasing rapidly. Here, we performed a retrospective study evaluating the prevalence of Salmonella harboring armA-mediated aminoglycoside resistance in community-acquired infections and in food or environmental sources. The prevalence rates of armA-harboring Salmonella strains were 1.1/1,000 (13/12,095) and 8.7/1,000 (32/3,687) in outpatient and food/environmental isolates, respectively. All the armA-harboring Salmonella strains were resistant to multiple drugs, including fluoroquinolone and/or extended-spectrum cephalosporins, and most (34/45) belonged to serovar Indiana. The armA genes of these strains were all carried on plasmids, which spanned five replicon types with IncHI2 being the dominant plasmid type. All the armA-carrying plasmids were transferable into Escherichia coli and Acinetobacter baumanii recipients. The conjugation experiment results revealed that the armA-harboring S. Indiana strains had a relatively higher ability to acquire armA-carrying plasmids. The low similarity of their pulsed field gel electrophoresis patterns indicates that the armA-harboring Salmonella strains were unlikely to have originated from a single epidemic clone, suggesting broad armA spread. Furthermore, the genetic backgrounds of armA-harboring Salmonella strains isolated from outpatients exhibited higher similarity to those isolated from poultry than to those isolated from swine, suggesting that poultry consumption maybe an infection source. These findings highlight an urgent need to monitor the prevalence and transmission of armA-harboring Salmonella, especially S. Indiana, to better understand the potential public health threat and prevent the further spread of these strains.